Peran Organizational Identification Sebagai Mediator Pengaruh Job Insecurity Terhadap Islamic Organizational Citizenship Behavior dan Kinerja Karyawan - Andi Nur Azizah Hafsah; Muafi Muafi (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2022)
Background - PT. Long Bagun Prima Sawit is a company that runs in the oil palm plantation industry often gets a public spotlight. News with a viewpoint that is not profitable for PT. Long Bagun Prima Palm This is certainly indirectly can affect the behavior and performance of its employees. Likewise, the opposite, news or the company's positive image will also make proud employees with a high level of organizational identification. Aim - This study tested and analyzed the influence of job insecurity against Islamic OCB and employee performance mediated by organizational identification. Design / Methodology / Approach - The research approach used in this study was a quantitative approach by distributing questionnaires to respondents. The population studied in this study were employees of PT. LNG Bagun Prima Sawit totaling 78 people. The data analysis method used in this study is Structural Equation Model (SEM) using the Partial Least Square (pls). Results and Discussion - The results of this study indicate that the job insecurity has a negative effect on organizational identification. This shows that the higher the level of job insecurity felt by employees, the level of self-identification of employees of the company will decline so even the opposite. While organizational identification has a positive effect on Islamic OCB and employee performance. When employees identify themselves with the company, the Islamic OCB behavior and employee performance will be maximal. In addition, organizational identification also proved to mediate job insecurity with Islamic OCB and employee performance. High self-identification of the company will weaken the negative influence of job insecurity and increase the Islamic OCB behavior and employee performance. Conclusion - Organizational Identification is proven to have a positive effect on Islamic OCB. Organizational identification is proven to have a positive effect on employee performance, but job insecurity is proven to have a negative effect on organizational identification. While organizational identification is proven to mediate the influence of job insecurity against Islamic OCB and employee performance. Research Implication - The implications of this study provide an overview of companies to further emphasize organizational identification because it is proven to provide good influence both Islamic OCB and employee performance. In order to grow organizational identification in the company, the employee job insecurity must be minimized.